SMEs in the Philippine manufacturing industry and globalization meeting the development challenges - Aldaba, Rafaelita M. ([Quezon City] School of Economics, University of the Philippines, 2009)
In view of rapid changes in the international trade and the growing complexity of the global production trade and the global production system, this paper reviews the government's small and medium enterprises (SME) policies in the manufacturing sector. It shows that despite the number of policies and programs to improve firm competitiveness, the performance of SMEs has not been vigorously enough to boost the manufacturing industry. [This paper also] highlights the importance of creating a separate government office that would coordinate SME policies and programs to support the integration of SMEs in the global production chain.
This paper appeared as chapter 8 of the Economic Research Institute for ASEAN and East Asia (ERIA) Research Project Report 2007 no.5, Asian SMEs and Globalization edited by Dr. Hank Lim.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 186-188)
Keywords: Small business -- Philippines -- Government policy; Manufacturing industries -- Philippines -- Government policy; Automobile industry and trade -- Philippines; Electronic industries -- Philippines -- Government policy; Clothing trade -- Philippines -- Government policy